Management strategies for multi-use recreational fisheries: coexistence of kokanee and trophy lake trout in western waters - Pate, William M., author; Johnson, Brett, advisor; Kendall, William, committee member; Lepak, Jesse, committee member; Teel, Tara, committee member (Colorado State University. Libraries, 2013)
Kokanee Oncorhynchus nerka are stocked in coldwater reservoirs throughout the western United States for sport fishing and they are a popular fish for both managers and anglers alike. Lake trout Salvelinus namaycush have also been introduced to many western reservoirs, partly because they can attain relatively large sizes (> 30 kg). These piscivores require a large, high quality forage base to sustain high growth rates, and kokanee can fulfill this requirement. However, where lake trout and kokanee co-occur, lake trout often grow in size and numbers and their consumptive demand increases beyond the capacity of the kokanee population to support. Consequently, kokanee abundance declines followed by precipitous declines in lake trout growth and body condition. My work focused on finding a management strategy that could produce sustainable fisheries for both in Blue Mesa Reservoir, Colorado, where lake trout appear to have diminished kokanee abundance. In 2009, managers began a lake trout removal program in an attempt to achieve the primary management goal of a sustainable, hatchery-dependent kokanee population and the secondary goal to provide a trophy lake trout fishery. I developed an age-structured kokanee population model using estimates of natural mortality, harvest, and predation from lake trout with a fixed annual stocking quota of kokanee fry. Age-specific estimates of natural and fishing mortality were estimated using an allometric model and creel survey, respectively. I then determined lake trout consumptive demand on the kokanee population with a bioenergetics model by estimating lake trout abundance, growth rates, diet, and energy densities of predator and prey species. Then alternative management scenarios to reduce lake trout consumptive demand were evaluated using the Fishery Analysis and Modeling Simulator parameterized for the Blue Mesa Reservoir lake trout population. After estimating the current level of lake trout removal (μ = 0.231 for age-4 through age-9), it was incrementally increased to determine the level that allowed for a stable kokanee population (μ = 0.381). The simulations suggested that removal of lake trout must be intensified if kokanee and fast-growing lake trout are to persist in Blue Mesa Reservoir, Colorado.
Keywords: kokanee; predator-prey interactions; population dynamics modeling; lake trout